New insights into the relationship of parasitic quill mites and birds: Picobia species in Asian and New World Barbets - M. Skoracki; B. Sikora; M. Unsoeld; M. Hromada; Z. Kwieciński (The European Zoological Journal)
Quill mites are obligatory parasites of birds, widely distributed among their hosts. For the first time, we examined birds from two small, phylogenetically closely related piciform families, Megalaimidae (New World Barbets) and Capitonidae (Asian Barbets), for infestation by parasitic mites of the subfamily Picobiinae (Acariformes: Syringophilidae). Birds of the family Megalaimidae were infested by two new species of the genus Picobia: Picobia insolita Skoracki, Sikora & Unsoeld n. sp. collected from Caloramphus hayii in Indonesia, and Picobia paraheeri Skoracki, Sikora & Unsoeld n. sp. found on nine bird species of the genus Psilopogon, including P. zeylanicus in Sri Lanka, P. asiaticus in India, P. virens in China, P. franklini and P. lineatus both in Nepal, and P. corvinus, P. rafflesii, P. chrysopogon, P. pyrolophus, all in Indonesia. Within the Capitonidae family, a single quill mite species, Rafapicobia olszanowskii Skoracki et al. 2020, was found infesting two species of the genus Capito, i.e. C. maculicoronatus in Panama and C. niger in Surinam and Guyana, and these two Asian Barbet species are new hosts for this quill mite species. Our further analysis of picobiine mite records associated with the entire order of Piciformes revealed a correlation between the mites’ distribution patterns and the phylogeny of piciform birds. This significant congruence suggests a close evolutionary relationship between picobiine mites and their avian hosts.http://zoobank.org/urn:lsid:zoobank.org:pub:F9DEB980-6481-4229-A071-52AC9FF69879http://zoobank.org/urn:lsid:zoobank.org:act:6B4F98EB-D166-4DBF-B26F-49F4B22903A8http://zoobank.org/urn:lsid:zoobank.org:act:98140DAC-5C53-438B-85A6-1FBA52D178D0